2002
DOI: 10.1161/01.res.0000047507.22487.85
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Adenine Dinucleotide Phosphate Mediates Ca 2+ Signals and Contraction in Arterial Smooth Muscle via a Two-Pool Mechanism

Abstract: Abstract-Previous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
124
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(149 citation statements)
references
References 37 publications
22
124
3
Order By: Relevance
“…In paired cells, intracellular dialysis of NAADP-free pipette solution had little or no effect (n ϭ 17; not shown). Our findings are consistent with the view that the events leading up to the initiation of global Ca 2ϩ waves by NAADP are complex, in that there is a highly localized release of Ca 2ϩ , which precedes the global Ca 2ϩ waves and the associated contractile response (13). In general, this initial localized Ca 2ϩ release event appears as 1) a uniform increase in Fura-2 fluorescence ratio around the entire perimeter of the cell ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In paired cells, intracellular dialysis of NAADP-free pipette solution had little or no effect (n ϭ 17; not shown). Our findings are consistent with the view that the events leading up to the initiation of global Ca 2ϩ waves by NAADP are complex, in that there is a highly localized release of Ca 2ϩ , which precedes the global Ca 2ϩ waves and the associated contractile response (13). In general, this initial localized Ca 2ϩ release event appears as 1) a uniform increase in Fura-2 fluorescence ratio around the entire perimeter of the cell ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with this proposal, the enzymes for the synthesis and metabolism of NAADP (5,6) and cyclic ADP-ribose (7) have been shown to be associated with smooth muscle in addition to other cell types. In smooth muscle, cyclic ADP-ribose may mobilize Ca 2ϩ from the SR by activating RyRs (8 -12), whereas our studies on arterial smooth muscle (13) are consistent with the idea that NAADP mobilizes Ca 2ϩ from an undefined store that may be coupled to the SR (14 -16). Briefly, we have demonstrated that NAADP triggers spatially restricted Ca 2ϩ bursts in arterial smooth muscle, which subsequently elicit a global Ca 2ϩ wave and muscle contraction by CICR via RyRs (13).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…These enzymes also possess a transglycosidation (base-exchange) activity capable of exchanging the nicotinamide moiety of NAD(P) with nicotinic acid or other nucleophiles. In the presence of nicotinic acid and NADP, the base-exhange reaction of the ADP-ribosyl cyclase family is responsible for generating nicotinic acid adenine dinucleotide phosphate (NAADP), another compound capable of regulating calcium release from intracellular stores in a variety of cell types, including those of some smooth muscles (57)(58)(59)(60)(61)(62).…”
Section: Adp-ribosyl Cyclase Cd38 and Cyclic Adp-ribose In Airway Smentioning
confidence: 99%